Nuclear Factor κB (NF-κB)–Mediated Inflammation in Multiple Sclerosis - Zhou, Yifan; Cui, Chunping; Ma, Xiaoyu; Luo, Wenjing; Zheng, Song Guo; Qiu, Wei (Frontiers in Immunology, 2020)
The nuclear factor kappa B (NF-κB) signaling cascade has been implicating in a broad range of biological processes, including inflammation, cell proliferation, differentiation and apoptosis. The past three decades have witnessed a great progress in understanding the impact of aberrant NF-κB regulation on human autoimmune and inflammatory disorders. In this review, we discuss how aberrant NF-κB activation contributes to multiple sclerosis (MS), a typical inflammatory demyelinating disease of the central nervous system (CNS), and its involvement in developing potential therapeutic targets